Strategi Pengembangan Agribisnis Cabai Merah Dikawasan Agropolitan Kabupaten Serang - Sulaeni, Sulaeni; Wibowo, Aris Suprio (JURNAL AGRIBISNIS TERPADU, 2018)
Development Strategy in the Serang Regency Agropolitan Area. The goal of this research is : (1) To research the income of red chili farming in the Serang Regency agropolitan area, (2) To analyze the factors of production costs that affect the income of chili farming in the Agropolitan area of Serang regency (3) To find out the strategy for developing red chili farming in the agropolitan area of Serang Regency..Research method that used was observation and data registration that analyzed was secondary data, got from interview result of farmer. The sample was 30 farmers. Method of analysis that used: (a) analysis of clean income was difference of gross income reduced total production cost. (b) analysis of linier regression multivariate to explain influence of cost variable of seed, fertilizer, pesticide, manpower, mulsa, towards net income. (c) SWOT analysis.Result of analysis shows that in one season chili farmer at agropolitan area of Serang regency income Rp. 53,881,058.84/hectare. Result of regression analysis in red chili farming research at agropolitan area of Serang regency was Y=6,213+0,435X1-0,338X2+0,136X3+0,017X4-0,404X5+1,031X6 .Seeds, fertilizers, mulch, and labor are very influential on the income of red chili farming. If the measurement of 4 factors is not in accordance with the five farms, it can affect or decrease farmers income. Based on the results of the SWOT analysis with the value indicated that the difference in opportunity and threat is 0.92, while the difference between strength and weakness is 0.82. Then the strategy of developing red chili in the Agropolitan area of Serang Regency is in quadrant I.